Pengaruh Penggunaan Limbah Beton Sebagai (Agregat Halus) Terhadap Uji Kuat Tekan Paving Block: The Effect Of Using Concrete Waste As (Fine Aggregate) On The Test Of Paving Block Compressive Strength - Setiawan, Andry; Rahmawati, Rahmawati; Adnan, Adnan (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
In Indonesia, the use of construction waste is usually not utilized properly most are simply dumped in open fields, and some are used as backfill material. The availability of such materials is vast. The purpose of this research is to determine the compressive strength value of paving blocks that utilize concrete waste with variations in the use of concrete waste, namely: 0%, 10%, 20, 30%, and the value of water absorption in paving blocks that utilize concrete waste with variations in the use of concrete waste, namely: 0%, 10%, 20, 30%. The test results showed that at 28 days of soaking, the compressive strength of normal paving blocks was 16.15 MPa, at 10% substitution of concrete waste for stone ash was 29.17 MPa, at 20% substitution of concrete waste to stone ash amounted to 39.32 MPa, and at 30% substitution of concrete waste to stone ash amounted to 22.66 MPa. From the results of the absorption test, it was found that the absorption value of normal paving blocks was 3.88%, at 10% substitution of concrete waste was 2.30%, at 20% substitution of concrete waste for stone ash was 1.89%, and at 30% substitution of concrete waste for stone ash was 2.80%.